O metacinema norte-americano e o storytelling: de Orson Welles a David Lynch - Chinita, Fátima (2013)
ABSTRACT: The American metacinema which, by tradition, is narrative but extremely formulaic favours the story above the telling. No man contributed more to alter this state of affairs than Orson Welles, whose cinematic practice exalted the filmic enunciation and linked it more explicitly to the narrative intentions of the creator, making it obvious that metanarrative is synonymous with metacinema. With Citizen Kane (1941), in particular, the cinema was made more disnarrative, as meant by French writer/director Alain Robbe–Grillet, well ahead of Modernism. The fragmented narration, the temporal convolutions, a tendency for paradox and the interpretative obstacles all come together to anticipate the serial practice of David Lynch in his last four features. Structuring the films in segments which constitute different but complementary versions of the same events, Lynch manages to express the director’s enunciation along with the narration of the characters, reinforcing the role of the telling in the midst of the story. In INLAND EMPIRE (2006) the use of mise-en-abyme as a way of duplicating stories and tellers further increases the objective and complicates what is clearly the reign of the puzzle or mind-game film. In the footsteps of Welles, Lynch contributed for an outbreak of metanarrative / metacinematic crossover indie films closer to the European aesthetic practice but still very much within the American narrative tradition.